What Makes Who Choose What Languages to Whom?: Language Use in Japanese-Filipino Interlingual Families in Japan - Yamamoto, Masayo (International journal of bilingual education and bilingualism, 2005)
This paper examines the language use of a small group of interlingual families of a Japanese parent and a Filipino parent with their offspring living in Japan and qualitatively explores possible explanations for their particular language use. Although the data collected from the subject group are limited, the data analysis does reveal some interesting features regarding language use among the family members: a less frequent use of the Filipino parent's native language(s) in comparison to the Japanese parent's native language and the employment of a language other than either parent's native language(s). These features in the present group greatly contrast with those of the Japanese-English interlingual families that the author previously investigated. Coupled with findings from the author's previous studies, findings from the present study suggest that the how and why of language use in interlingual families might be language-sensitive and not necessarily straightforward reflections of such linguistic considerations as the relative language proficiencies of the family members or access to a language community in the close vicinity.